DAMPAK DAN ANTISIPASI KEBAKARAN HUTAN - Lestari, Sri (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
Meteorological and Geophisical in Indonesia) on concentration pollutant Sulfur Oxides, particulate SO4= and smoke in accurrences of forest fire for September 1997 inThe frequent accurrences of forest fire causes air pollution. Concentration Sulfur Oxides, particulate SO4 = and smoke endangers the inhabitant’s health, and also decreases amount of rainfall. The result of observation by BMG (Institute of Kalimantan and Sumatera showed the increase to 700 % pollutant smoke, 313 % molecular cation NH4++ , Ca+ , Mg++ and 540 % anion Cl- , NO- and SO4— And UPT- HB, BPPT to do rainmaking for disperse the smoke.